2015
DOI: 10.1074/jbc.c115.671107
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase (MMP) Proteolysis of the Extracellular Loop of Voltage-gated Sodium Channels and Potential Alterations in Pain Signaling

Abstract: Background:Mutations in the voltage-gated sodium channel Nav1.7 cause congenital insensitivity to pain (CIP) in humans. Results: Missense mutation R907Q in the extracellular disordered loop of Nav1.7 may also cause CIP because of the enhanced MMP-9 proteolysis of the mutant. Conclusion: Accelerated cleavage of Nav1.7 by MMP-9 explains insensitivity to pain. Significance: MMP proteolysis of sodium channels is a novel biochemical phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…(1) By modulating Schwann cell signaling and number in the damaged nerve, MMPs control the length of myelin internodes and relative localization of nodal proteins [18, 4345]. (2) By proteolysis of contractile, adhesive and ion channel proteins, including laminin, dystroglycan, sodium channels and NMDA receptor [17, 18, 34, 4648], MMP may directly regulate the mechanosensitive machinery of A-afferents. (3) Because of the enhanced MMP proteolysis in the injured PNS, the liberated MBP peptides concentrate at the paranodal/nodal areas [4, 7], as part of pro-algesic immune complexes [6, 7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(1) By modulating Schwann cell signaling and number in the damaged nerve, MMPs control the length of myelin internodes and relative localization of nodal proteins [18, 4345]. (2) By proteolysis of contractile, adhesive and ion channel proteins, including laminin, dystroglycan, sodium channels and NMDA receptor [17, 18, 34, 4648], MMP may directly regulate the mechanosensitive machinery of A-afferents. (3) Because of the enhanced MMP proteolysis in the injured PNS, the liberated MBP peptides concentrate at the paranodal/nodal areas [4, 7], as part of pro-algesic immune complexes [6, 7].…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms of the nociceptive MT1-MMP activity may include the release of the algesic cytokines or regulation of proteolysis and function of adhesion molecules and ion channels at the PNS injury site, segmental ganglia or spinal cord [4, 1316, 18, 34, 56]. If TIMP-2 compete with MT1-MMP antibody for the binding with MT1–MMP, the antibody excess may release free TIMP-2 to inhibit metalloproteinase activity or engage in trophic regulation [57] of nociceptive circuitry [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the substantial level of sequence homology among sodium channels, our data also implicated MMP proteolysis in regulating the cell surface levels of the Nav1.7, Nav1.6, and Nav1.8 channels, but not Nav1.9 in which the MMP-9 cleavage site is inactivated [85]. Based on our results that were inspired by the CleavPredict predictions, we suggested that the aberrantly accelerated MMP-9 proteolysis during neurogenesis was a biochemical rationale for the functional inactivation in Nav1.7 and that the enhanced cleavage of the Nav1.7-R907Q mutant was a cause of CIP in the Bedouin family.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, VGSC blockers decrease the invasive potential of cell by reducing the activity of proteases such as cathepsin E, kallikrein-10 and MMP-7, as well as total MMP[149]. Another stretch activated sodium channel Nav1.6 has been also reported to affect invadosomes activity since its blockade prevents ECM degradation by macrophages and melanoma cells[150].Not only ion channels can affect invadosome dependent matrix degradation but the MMP proteolysis can affect the clustering of the ion channels such as in the case of MMP9 proteolysis that has been shown also to regulate the cell surface levels of some VGSC[151].…”
mentioning
confidence: 99%